Organoleptic Test Of Yellow Pumpkin Puree Substitution On The Quality Of Puuf Pastry - Rahman, Afdalil; Faridah, Anni; Anggraini, Ezi; Andriani, Cici (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
Puff pastry is a delicious and savory food that is often made in hotels, has a soft texture that doesn't break easily when served, is layered, slightly dry and light brown in color, and has a distinctive aroma of fat, but the ingredients used are wheat flour. which is a material that is still imported with annual consumption reaching 6.2 tonnes in Adelia (2022), while in Indonesia the government recommends using local materials. To reduce the use of wheat flour, local food sources can be utilized, namely by using pumpkin which is processed into puree to be used as a partial replacement for the use of wheat flour (Nabilla et al 2021). This research aims to analyze the substitution of pumpkin puree for the quality of puff pastry as much as 20%, 30% and 40% for the quality of the shape, color, aroma, texture and taste of the puff pastry produced. This type of research is a pure experiment using a Completely Randomized Design method. The data used is primary data obtained directly from 3 expert panelists by filling in the organoleptic test format for the quality of puff pastry with the substitution of pumpkin puree. The data obtained was then tabulated in table form and Analysis of Variance (ANOVA) was carried out, if Fh>Ft then continued with the Duncan Test. The results of the study showed that there was a significant effect of using pumpkin puree of 20%, 30% and 40% on the quality of the texture (dry) and texture (crisp). The best result from the puff pastry quality test using pumpkin puree was 30%.